The persistence of Asante chieftaincy under colonial rule: explanations of an enigma - Mueller, Louise (Africana Studia, 2020)
The aim of this article is to provide a religious explanation for the persistence of Asante chieftaincy in Ghana during the colonial period (1896-1957) and beyond. Chieftaincy was the most common traditional political system in Africa before colonial rule. In the colonial period, in many African countries including Ghana the British colonial rulers introduced political superstructures, known as Indirect Rule, that were meant to control the African populations. As a consequence, African chieftaincies came under pressure during the decolonisation process, and those African leaders involved with the independence of their country aimed at clipping the wings of the traditional authorities. In the Ghanaian case, those leaders perceived the chiefs and queen mothers as outmoded rulers, who stood in their way to build modern African nations. It is therefore not self-evident that chieftaincy among the Asante in Ghana and other cultural groups in countries under former British Indirect Rule, such as Nigeria, Botswana, Lesotho and Swaziland has continued to exist. In this article, based on doctoral research at the University of Edinburgh, the investigator enhances insight in the religious roles of Asante traditional authorities in the colonial period to make the persistence of chieftaincy among the Asante understandable. The focus is on the religious mediatory and peacekeeping roles of these authorities and especially of the Asantehenes Prempeh I and II. The objective of the article is to increase our understanding of the religious roles of these Asante royals by making use of the concept of Indigenous Religion, which is relatively new in the field of religious studies. The concept of Indigenous Religion has replaced the older notion of African Traditional Religion, which was rightly attacked by Hobsbawn and Ranger as being an ‘invention of tradition’. The model of religious syncretism of the scholar of religions, Ulrich Berner, is introduced to enhance understanding of the hybrid forms between Asante Indigenous Religion and various forms of Islam and Christianity in Asante’s changing historical setting. The article furthermore shows that the Asante Kings Prempeh I and II, who were themselves deeply religious, managed to maintain influence and prestige by their indigenous religious negotiations with the inhabitants of the spiritual world and with the Islamic and Christian world religious leaders and their adherents. By mediation and performance of their religious roles the Asante Kings maintained or gained not all but sufficient adherents of various distinguished groups in Asante society, such as Christians and Muslims, the Asante royal servants (nhenkwaa) and the nouveau rich (akonkofoƆ). In conclusion, the resilience of Asante chieftaincy in the ‘Crown colony of Asante’ until the current day can be explained by the continuation of a – although significantly diminished – mediatory role held by the Asante traditional authorities. More important, however, its persistence is explainable through the increased significance of these authorities’ religious peacekeeping role. Keywords: Ghana, Asante, colonial era, chieftaincy, religion.